University Teachers’ Engagement in Academic Writing in Nepal (Pragyaratna प्रज्ञारत्न, 2025)
This research investigates the engagement of university teachers in research and publication activities at Tribhuvan University (TU) in Nepal. Utilizing a cross-sectional survey design, quantitative data from 473 teachers across 23 TU colleges were analyzed using the chi-square test Ficher’s exact test, and binary logistic regression. The results reveal a notably low level of engagement in research and publication activities among teachers. Teachers publish fewer papers in international/indexed journals compared to national journals. Urban location and Quality Assurance and Accreditation (QAA) certification correlate with higher engagement, contrasting with lower participation in rural settings, district towns, and non-QAA accredited institutions. The study recommends fostering an academic culture that motivates and empowers teachers for research and publication. Furthermore, gender, geographical location, and institutional type (QAA vs. non-QAA) are identified as significant factors shaping teachers’ research involvement and publications.